Nonomuraea stahlianthi sp. nov., an endophytic actinomycete isolated from the stem of Stahlianthus campanulatus - Nantawan Niemhom; Chanikul Chutrakul; Chanwit Suriyachadkun; Chitti Thawai (My University, 2017)
A novel endophytic actinomycete, designated strain SC1-1T, was isolated from sterilized stem tissue from Stahlianthus campanulatus collected in Udon Thani province, Thailand. The isolate formed short chains of spores on aerial mycelium and presented meso-diaminopimelic acid in the cell wall peptidoglycan. Glucose, madurose, mannose, rhamnose and ribose were observed as sugars in the cells. The cell membrane phospholipids were phosphatidylethanolamine, phosphatidylmethylethanolamine, hydroxy-phosphatidylethanolamine, diphosphatidylglycerol, phosphatidylinositol, phosphatidylinositol mannoside and ninhydrin-positive phosphoglycolipids. The major menaquinones were MK-9(H4) and MK-9(H2). The main cellular fatty acids were iso-C16:0, 10-methyl C17 : 0 and C17 : 1ω6c. A high G+C content (70.7 mol%) was present in the genomic DNA. The taxonomic position based on the 16S rRNA gene sequence analysis revealed that strain SC1-1T belonged to the genus Nonomuraea and shared the highest 16S rRNA gene sequence similarity value with Nonomuraea dietziae DSM 44320T (98.82 %), followed by Nonomuraea africana IFO 14745T (98.58 %), Nonomuraea jabiensis A4036T (98.43 %), Nonomuraea endophytica YIM 65601T (98.36 %), Nonomuraea purpurea 1SM4-01T (98.34 %), Nonomuraea angiospora IFO 13155T (98.29 %), Nonomuraea roseola IFO 14685T (98.23 %) and Nonomuraea recticatena IFO 14525T (98.23 %). On the basis of the DNA–DNA hybridization relatedness and including the physiological and biochemical characteristics, strain SC1-1T should be judged as a novel species of the genus Nonomuraea , for which the name Nonomuraea stahlianthi sp. nov. is proposed. The type strain is strain SC1-1T (=BCC 66361T=NBRC 110006T).
Keywords: Rhamnose; Genomics and Phylogenetic Studies